52. OUTCOMES OF LAPAROSCOPIC CHOLECYSTECTOMY FOR ACUTE CHOLECYSTITIS AFTER PERCUTANEOUS GALLBLADDER DRAINAGE AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Background: Percutaneous transhepatic gallbladder drainage has been recognized by many centers as an effective method for reducing gallbladder inflammation. It is considered a temporary treatment step prior to cholecystectomy or a definitive solution for patients with multiple surgical risk factors who are not candidates for surgery.Objectives: To evaluate the outcomes of laparoscopic cholecystectomy following gallbladder drainage. Subjects and Methods: A retrospective descriptive study was conducted on 35 patients with acute cholecystitis due to gallstones who underwent laparoscopic cholecystectomy after gallbladder drainage at the Hepato-Pancreato-Biliary Surgery Department, Thong Nhat Hospital, from January 2022 to May 2024.Results: The avervage age was 71.14 ± 12.6 years. The male-to-female ratio was 1.2:1. The rate of abdominal surgical history was 11.4% of cases, and comorbidities accounted for 91.4%, with cardiovascular disease (80%) and diabetes mellitus (40%) being predominant. ASA III classification was the most common, accounting for 42.9%. 28/35 patients (80%) underwent drainage within 72 hours after diagnosis. Most patients had their drains in place for over 6 weeks (85.75%). The average operating time was 128 ± 46.5 minutes, the average blood loss was 24.3 ± 15.3 ml. Intraoperative complications occurred in 5.8%, with one case (2.9%) of major bile duct injury and one case (2.9%) of duodenal injury. Postoperative complications were observed in 5.7%, including 2 cases of bile leakage. The average postoperative length of stay was 6.5 ± 2.6 days.Conclusion: Laparoscopic cholecystectomy following percutaneous gallbladder drainage has a high success rate and low rates of perioperative complications. Gallbladder drainage is an effective, easily performed, and safe treatment for cases of acute cholecystitis that are not suitable for surgery.
Keywords: Acute cholecystitis; Percutaneous gallbladder drainage; Laparoscopic cholecystectomy